2016
DOI: 10.1002/2015gl066978
|View full text |Cite
|
Sign up to set email alerts
|

Full‐wave modeling of EMIC waves near the He+ gyrofrequency

Abstract: Electromagnetic ion cyclotron (EMIC) waves are known to be excited by the cyclotron instability associated with hot and anisotropic ion distributions in the equatorial region of the magnetosphere and are thought to play a key role in radiation belt losses. Although detection of these waves at the ground can provide a global view of the EMIC wave environment, it is not clear what signatures, if any, would be expected. One of the significant scientific issues concerning EMIC waves is to understand how these wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
99
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(110 citation statements)
references
References 43 publications
9
99
2
Order By: Relevance
“…Such localization of the EMIC waves, which is predicted by Ref. [28], is similar to the LHP EMIC waves [12]. Ref.…”
Section: Epj Web Of Conferencessupporting
confidence: 82%
See 3 more Smart Citations
“…Such localization of the EMIC waves, which is predicted by Ref. [28], is similar to the LHP EMIC waves [12]. Ref.…”
Section: Epj Web Of Conferencessupporting
confidence: 82%
“…Ref. [12] suggested that polarization reversal and mode conversion occurs at the crossover frequency, where the left-hand (LHP) and right-hand (RHP) polarization modes cross each other in the dispersion relation, from LHP to RHP polarization and such RHP EMIC waves can propagate to the inner magnetosphere, which is consistent with 1D full-wave calculations [13,14].…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…In Earth's magnetosphere, as these waves propagate along B 0 , the wave normal angle increases and becomes nearly 90° when waves reach the Buchsbaum resonance. The waves then reflect toward a higher L-shell and lower magnetic latitude (Kim & Johnson 2015). Because both reflected IIH waves (Kim et al 2015a) and LHP EMIC waves (Kim & Johnson 2015) at the Buchsbaum resonance propagate to the different L-shells in the dipole field configuration, how 2D/3D heavier ion density structures in the planetary magnetosphere relate to propagation characteristics of the IIH and LHP EMIC waves remains as future work.…”
Section: Discussionmentioning
confidence: 99%